Mental Well-Being during the COVID-19 Confinement among Adolescents in Catalonia: The Role of Demographic and Other COVID-Related Variables - Cinta Folch; Helena González-Casals; Joan Colom; Marina Bosque-Prous; Tivy Barón-Garcia; Anaís Álvarez-Vargas; Jordi Casabona; Albert Espelt (MDPI AG, 2022)
This study aimed to describe the impact of the COVID-19 pandemic on the social situation, self-perceived health status, and mental well-being of adolescents in Catalonia during home confinement, and to evaluate factors that are associated with poor overall mental well-being. An online cross-sectional study among a cohort of students (14-18 years old) of central Catalonia (DESKcohort) was performed during June-July 2020. Poisson regression models with robust variance were used to identify variables associated with "poor overall well-being," measured by the short version of the Warwick-Edinburgh Mental Wellbeing Scale. Out of 303 participants, 42.1% reported a decrease in family income, and 32.8% a loss of parental employment due to the COVID-19 pandemic, and these percentages were higher among people living in low socioeconomic neighborhoods (53.3% and 43.2%, respectively). Overall, 56.8% presented a poor overall well-being. Participants reporting a decrease in their family's income (aPR = 1.33) and those knowing a close person or family who died of COVID-19 (aPR = 1.42) were more likely to report a poor overall well-being. This study highlights the patterns of inequality and social vulnerability for COVID-19 pandemic outcomes. Considering social inequalities, interventions are needed to mitigate the impact of COVID-19 pandemic on the physical and the psychological wellbeing of children and their families.